Development and Efficiency Analysis of Dual Active Bridge Converter Employing SiC Devices Using TMS 320F280039 - T. Deepti; K. Deepa; Albert Alexander Stonier; Geno Peter; A. Anoop; Vivekananda Ganji (IET Circuits, Devices and Systems)
The utilization of on-board chargers (OBCs) in electric vehicle (EV) has become increasing prevalent due to their configuration and cost-efficiency in the context of installation. Furthermore, the automobile industry is increasingly showing interest in bidirectional power flow because of the EV’s ability to provide energy back to the network. The paper presents an analytical method for designing the crucial elements of dual active bridge (DAB) with single-phase shift (SPS) modulation control. By comparing the estimated energy efficiency characteristics with measurements from a prototype 90-W single-phase DAB converter fitted with silicon carbide (SiC) MOSFETs, the robustness of this approach is exemplified and loss, and efficiency comparison analysis is carried out with conventional switching devices. Furthermore, this study presents a closed-loop voltage controller that effectively regulates the output voltage in the presence of significant variations in both the input line and load conditions. Finally, a comparison analysis is undertaken to evaluate important factors such as overall efficiency and settling time across different load circumstances. This analysis provides substantial perspectives toward the actual functionality of these systems through contrasts of simulation results with hardware-based results from the real world.